PERIPHERAL NERVE IMPAIRMENT PREDICTS FALLS AND INJURIOUS FALLS IN WOMEN: STUDY OF WOMEN'S HEALTH ACROSS THE NATION. (11th November 2018) - Ylitalo, K; Karvonen-Gutierrez, C; Peng, M; Pettee Gabriel, K; Lange-Maia, B; Strotmeyer, E
Abstract: Falls and related injuries are an important public health concern and are underappreciated in early aging. This study examined the association between peripheral nerve impairment (PNI) and falls in early old age. Women (n=1, 973; median age 65.4 years) from the longitudinal cohort Study of Women's Health Across the Nation completed a peripheral neuropathy symptom questionnaire and 10-g standard monofilament testing in 2015; PNI was defined as ≥4 self-reported symptoms or monofilament insensitivity. Falls and injurious falls in the previous 12 months were assessed via questionnaire. Generalized estimating equations were used to generate adjusted prevalence ratios (PR) and corresponding 95% confidence intervals (CI). The prevalence of PNI was 25.3%, 29.5% reported ≥1 fall, and 18.0% reported ≥1 injurious fall. Women with PNI were more likely to report falls (39.5% vs. 27.3%; p<0.001) and injurious falls (23.9% vs. 17.1%; p=0.01) compared to women without PNI. Fall prevalence (PR=1.45; 95%CI:1.25–1.68) was higher for women with PNI, and in stratified analyses by diabetes status (Diabetes PR=1.50, 95%CI:1.14–1.98; Non-diabetes PR=1.36, 95% CI:1.14–1.63). Injurious fall prevalence (PR=1.40; 95%CI:1.14–1.72) was higher among women with PNI, although after stratifying by diabetes status, PNI was associated with injurious falls among only women without diabetes (PR=1.45; 95%CI:1.14–1.84). Neuropathy screening instruments may identify women in early old age at high risk for falls and fall injuries, regardless of diabetes status. Future work should consider the utility of assessing frequency and severity of PNI symptoms for fall screening in early aging populations, prior to risk for more severe injuries in late life.